TANAMAN BERPERAWAKAN RENDAH DAN MEMBELIT DI PEKARANGAN TELUKNAGA, CITEUREUP DAN PACET - SUTARNO, H.; ROEMANTYO, H.; SUPARDIJONO, E.K. (BERITA BIOLOGI, 1985)
H. SUTARNO, H. ROEMANTYO & E.K. SUPARDIJONO. 1985. Plants with lowly statures in the kitchen gardens in Teluknaga, Citeureup and Pacet. Berita Biologi 3 (2): 49 - 54. Studies on kitchen garden crops of the lower stratum (3m) including climbing plants were carried out in Teluknaga (0-10m), Citeureup (200-500m) and Pacet (600-1400). These studies were aimed at obtaining information on species variation, cultivation and utilization. The species number in those three subdistricts were 14, 36 and 37 species, respectively. Among the most commonly observed crops were chilipepper, pineapple, sugarcane, coco-yam, cassava and taro. The relatively good soil and climatic conditions as well as reasonably large habitants being farmers, the home-gardens in Ci-1 teureup and Pacet enabled the owners to fully utilize their home-gardens for agriculture.